2021
DOI: 10.3390/ani11041169
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Effects of cis-9,trans-11- and trans-10,cis-12-CLA on Immune Regulation in Ruminal Epithelial Cells

Abstract: In this study, we used transcriptomics and qPCR to investigate the potential immunoprotective effects of different conjugated linoleic acid (CLA) isomers, the natural rumen microbial metabolites, on lipopolysaccharide (LPS)-induced inflammation of ruminal epithelial cells (RECs) in vitro. The results showed that 100 μM trans-10,cis-12-CLA exerted higher anti-inflammatory effects than cis-9,trans-11-CLA by significantly downregulating the expression of genes related to inflammation, cell proliferation and migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Maurice-Van Eijndhoven et al [18], when comparing four breeds bred in the Netherlands, revealed a clear and significant difference in the concentration of short-and medium-chain acids and linoleic acid (C18:2c9,t11), and in the percentage of fat in milk. Carroll et al [14] and Ramalho et al [19] observed similar differences between breeds in milk fat composition and concentration. The advent of technologies for relatively inexpensive whole-genome genotyping of cows makes it possible to study genetic changes in cattle in order to study the genetic architecture of trans fatty acids in cow's milk.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Maurice-Van Eijndhoven et al [18], when comparing four breeds bred in the Netherlands, revealed a clear and significant difference in the concentration of short-and medium-chain acids and linoleic acid (C18:2c9,t11), and in the percentage of fat in milk. Carroll et al [14] and Ramalho et al [19] observed similar differences between breeds in milk fat composition and concentration. The advent of technologies for relatively inexpensive whole-genome genotyping of cows makes it possible to study genetic changes in cattle in order to study the genetic architecture of trans fatty acids in cow's milk.…”
Section: Introductionmentioning
confidence: 72%
“…Milk TFAs are natural and are able to provide many health benefits, including boosting immune function, reducing excess fat, and completely removing or slowing down the process of neoplasm of tumors of various types of cancer [14,15]. This information warrants further research as it suggests that naturally occurring TFAs are metabolized very differently from industrially produced ones [15].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted from the treated cells (NC, LPS, L-Morusin+LPS and H-Morusin+LPS, respectively) (n = 4, respectively) using the RNA Pure Kit (Aidlab Biotechnologies Co., Ltd., Beijing, China) according to the manufacturer's instruction. cDNA was further synthesized using the PrimeScript RT Reagent Kit (Takara, Dalian, China), and qPCR was then performed with SYBR green in the ABI 7500 (Life Technologies, Singapore) using the previously described procedures [45]. The results were finally nor-malized to the expression of housekeeping genes tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) using the 2 -∆∆Ct method [45].…”
Section: Rna Extraction and Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
“…cDNA was further synthesized using the PrimeScript RT Reagent Kit (Takara, Dalian, China), and qPCR was then performed with SYBR green in the ABI 7500 (Life Technologies, Singapore) using the previously described procedures [45]. The results were finally nor-malized to the expression of housekeeping genes tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) using the 2 -∆∆Ct method [45]. All the primers used were designed using the Basic Local Alignment Search Tool [BLAST; National Center for Biotechnology Information (NCBI), Bethesda, MD, USA] and outlined in the Table S1.…”
Section: Rna Extraction and Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%